Anatomical structure interpretation of the effect of soil environment on fine root function - Tianyi Li; Jingjing Ren; Wenchun He; Yu Wang; Xiaochen Wen; Xiao Wang; Mengting Ye; Gang Chen; Gang Chen; Kuangji Zhao; Kuangji Zhao; Guirong Hou; et al. (Frontiers in Plant Science, 2022)
Fine root anatomy plays an important role in understanding the relationship between fine root function and soil environment. However, in different soil environments, the variation of fine root anatomical structure in different root sequences is not well studied. We measured the soil conditions and anatomical structure characteristics (root diameter, cortical tissue, vascular tissue and xylem) of fine roots of Cupressus funebris in four experimental sites, and analyzed each level of fine roots separately. We link these data to understand the relationship between fine root anatomy and soil conditions. We found that the anatomical structure of fine roots is closely related to soil environmental factors. The fine roots of lower root order are mainly affected by soil nutrients. Among them, the cortical tissue of first-order fine roots was positively correlated with potassium and phosphorus, but negatively correlated with nitrogen, while second- and third-order fine roots was positively correlated with soil total potassium and negatively correlated with nitrogen and phosphorus. For the fine roots of high root order, the cortical tissue disappeared, and the secondary vascular tissue was mainly affected by soil moisture. In addition, we also found that the division of fine root functional groups is not fixed. On the one hand, the function of third-order fine roots will slip. For example, the decrease of soil moisture will promote the transformation of third-order fine roots into transport roots, and the reduction of nitrogen will promote the transformation of third-order fine roots into absorption roots to fix nitrogen. This transformation strategy can effectively prevent the restriction of soil nutrients on plant growth. On the other hand, with the change of habitat, the first- and second-order fine roots are still the absorbing root, and the fourth- and fifth-order fine roots are still the transport root, but the efficiency of absorption and transport will be affected. In conclusion, our findings emphasize the fine roots in different soil environment to show high levels of plasticity, shows that fine root anatomical structure changes may make plants, and reveals that the fine is just order of reaction and its mechanism in the soil environment.